Evaluation of bilateral deficit in isometric contractions of the knee extensors - Antonio Carlos Moraes; Cláudia Silveira Lima; Bruno Tomasi Kuckartz; Cíntia Ehlers Botton; Ronei Silveira Pinto; Martim Bottaro (Universidade Federal de Santa Catarina, 2012)
Strength training has been reported as an important tool for enhancing and maintaining health. Resistance exercises can be executed unilaterally or bilaterally. Some studies have reported lower strength and electromyography (EMG) signal values in bilateral conditions than the sum of these values in unilateral conditions. This difference in strength and EMG is called the bilateral deficit. The aim of this study was to evaluate the strength and EMG activity of the rectus femoris and vastus lateralis during unilateral and bilateral isometric knee extension. The sample consisted of 10 non-resistance trained males aged 18 to 30 years. Strength and EMG were recorded through use of a load cell and surface electrodes, respectively. A 120° knee extension was used for the isometric knee extension test. The results showed significantly higher values for strength and EMG signal (p <0.05) in unilateral conditions, as well as bilateral deficit in both strength and EMG signal. These results suggest that unilateral training promotes greater muscle stimulation, and can thus represent an important strategy to be used in the prescription of strength training exercises.